Fear and Anxiety in Pregnant Women During the COVID-19 Pandemic: A Systematic Review - Francisco Javier Muñoz-Vela; Francisco Javier Muñoz-Vela; Luciano Rodríguez-Díaz; Juan Gómez-Salgado; Juan Gómez-Salgado; Francisco Javier Fernández-Carrasco; Regina Allande-Cussó; Juana María Vázquez-Lara; Javier Fagundo-Rivera (Frontiers Media S.A., 2023)
Objectives: The aim of this study was to explore the impact of the 2020-2022 pandemic on the levels of fear and anxiety in pregnant women and to identify risk and protective factors.Methods: A systematic review was conducted. Electronic databases were consulted for studies published between January 2020 and August 2022. The methodological quality was assessed using a critical appraisal tool for non-randomised studies.Results: Seventeen studies were included in the review. A high prevalence of levels of fear and anxiety were observed. Risk factors such as unplanned pregnancy, poor support from partners, or intolerance of uncertainty were identified for high levels of fear. Regarding anxiety, risk factors such as maternal age, social support, financial status, or concern about being able to maintain antenatal follow-ups were identified.Conclusion: The COVID-19 pandemic had a significant impact on the mental health of pregnant women through increased levels of fear and anxiety. It has not been possible to establish a relationship between significant factors such as gestational age or health emergency control measures with high levels of fear or anxiety.